Proposal of in situ parameters for the assessment of physical vulnerability to seismic events: A Peruvian case study - Izquierdo Horna, Luis Antonio (2021)
After the last seismic event that occurred in Pisco, Peru in 2007 (7.9 Mw), the fragility of the structural conditions of the existing houses in the Peruvian territory became evident. Therefore, it is important to be able to anticipate or recognize those dwellings that are more physically vulnerable in order to preserve the livelihoods and living conditions of the residents. In this sense, the instruments currently used for this purpose do not guarantee an adequate assessment of reality. Thus, the objective of this research is to propose a set of parameters to determine the level of physical vulnerability present for a given sector based on its structural and constructive characteristics. For this purpose, it was necessary to determine the structural typology of the sector based on the predominant material, number of floors, structural damage and the construction process stage. This information will allow the selection of a set of parameters potentially capable of adequately identifying the level of physical vulnerability in the dwelling. The district of Los Olivos was chosen as a case study. This research resulted in a set of parameters grouped into the following categories: construction system, irregularity and soil condition, roofing system, structural interaction and state of conservation. These categories and their descriptors are applicable and reproducible at different territorial scales.